2006
DOI: 10.1111/j.1574-695x.2005.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of serine peptidase by a clinical strain ofCandida albicans: influence of growth conditions and cleavage of human serum proteins and extracellular matrix components

Abstract: Candida albicans expresses a vast number of hydrolytic enzymes, playing roles in several phases of yeast-host interactions. Here, we identified two novel extracellular peptidase classes in C. albicans. Using gelatin-sodium dodecyl sulfate polyacrylamide gel electrophoresis two gelatinolytic activities were detected at physiological pH: a 60-kDa metallopeptidase, completely blocked by 1,10-phenanthroline, and a 50-kDa serine peptidase inhibited by phenylmethylsulfonyl fluoride. In an effort to establish a proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…This suggests that at a higher pH, when the activity of SAP2 is reduced, other proteinases take over its role. These may include other C. albicans SAPs with more neutral pH optima, such as the SAP4-6 subset (Naglik et al , 2003a ), or serineor metalloproteinases that occasionally have been reported to occur in this yeast species (Rodier et al , 1999 ;dos Santos et al , 2006 ). Nevertheless, the current study strongly suggests that SAP2 can play the kinin-releasing role in some infections in niches of low pH such as stomach, vagina or urinary tract and/or where this protease dominates over the other SAPs.…”
Section: Discussionmentioning
confidence: 67%
“…This suggests that at a higher pH, when the activity of SAP2 is reduced, other proteinases take over its role. These may include other C. albicans SAPs with more neutral pH optima, such as the SAP4-6 subset (Naglik et al , 2003a ), or serineor metalloproteinases that occasionally have been reported to occur in this yeast species (Rodier et al , 1999 ;dos Santos et al , 2006 ). Nevertheless, the current study strongly suggests that SAP2 can play the kinin-releasing role in some infections in niches of low pH such as stomach, vagina or urinary tract and/or where this protease dominates over the other SAPs.…”
Section: Discussionmentioning
confidence: 67%
“…Conserved cysteine residues are probably implicated in maintaining the three-dimensional structure of the enzyme [31] . The SAP genes are differentially expressed depending on the C. albicans strain and environmental conditions [32][33][34][35][36] (Figure 1). For instance, eight of these proteases (Saps1-8) are secreted into the extracellular environment, while Sap9 and Sap10 are membrane GPIanchored proteins [37] .…”
Section: Albicansmentioning
confidence: 99%
“…This phenomenon is clearly observed in C. albicans yeast cells when cultured under chemically defined medium containing large proteins (e.g. albumin and hemoglobin) as a unique nitrogenous source, but not when Candida cells are cultured in a medium containing an unlimited nitrogenous source [104][105][106][107][108] ; (2) Some intracellular aspartic proteases produced by microorganisms also control the cleavage of important own proteins in order to promote protein activation and/or perfect functioning of a biosynthetic route; their inhibition can arrest signaling events and/or metabolic pathways, as a result inhibiting some crucial biological processes for microbial cells such as morphogenesis or expression of surface molecules responsible for adhesion or fungal protection. For example, some of these aspartic protease inhibitors alter the lipid biosynthesis, including ergosterol, resulting in altered membrane permeability [68,72,83] .…”
Section: F Pedrosoimentioning
confidence: 99%